ESTIMASI FUNGSI PERMINTAAN DAN ELASTISITAS PERMINTAAN BERAS DI PROPINSI SUMATERA UTARA - Saragi, Cyprianus PH.; Simbolon, Ramses; Siboro, Priscillia Arju M. (Jurnal Manajemen dan Bisnis, 2022)
Indonesia's agricultural sector has a very important role in the development of the national economy because most of the Indonesian people depend on the agricultural sector. This study aims to analyze the factors that influence the demand for rice and to analyze the elasticity of demand (price, cross, and income) of rice in the province of North Sumatra. The data used in this study is Time series data (1998-2018), data analysis using Multiple Linear Regression. The coefficient of determination (R2) of 0.82 indicates that about 82% of rice demand in North Sumatra can be explained by variations in rice prices, mung bean prices, egg prices, income per capita, and population, while the remaining 18% is explained by variations in other variables. which is not included in the model. The results of the over-all test show that the price of rice, the price of green beans, the price of eggs, per capita income, and the population have a significant effect on the demand for rice. Based on the partial test, the price of rice, the price of mung bean, and the population have a significant effect on the demand for rice, while the price of eggs and per capita income have no significant effect on the demand for rice in North Sumatra. The price elasticity of rice is inelastic, the cross elasticity of the price of green beans and the price of eggs is positive or substitution, and the income elasticity of rice is a normal good